Literature Review: Peran Telehealth sebagai Upaya Pencegahan Readmisi Pasien dengan Acute Miocard Infark - Meri Afridayani; Lailya Khusna; Khairati Siregar; Anggi Lukman Wicaksana (Politeknik Kesehatan Tanjung Karang, 2020)
Telehealth is an endeavor to prevent readmission in patients with Acute Miocard Infarct (AMI). The objective of this study was to identify the effect of Telehealth as a reoccurrence and readmission strategy for a patient with AMI. This study was a literature review with article searches in some databases including ScienceDirect, Sage Journals, Ebsco, Scopus, and Cochrane for the last ten years. The selected articles were limited to those in English with free full text. Studies that were involving adult AMI in the adult patient and obtaining intervention or monitoring via phone or Telehealth were included. The result from reviewed articles showed that Telehealth can be used as an alternative intervention to prevent readmission in patients with AMI. Various methods which are explained in the literature can be implemented as a strategy to prevent reoccurrence or readmission for the patient with AMI.